1999
DOI: 10.1093/emboj/18.6.1689
|View full text |Cite
|
Sign up to set email alerts
|

Self assembly of NuMA: multiarm oligomers as structural units of a nuclear lattice

Abstract: NuMA is a nuclear matrix protein in interphase and relocates to the spindle poles in mitotis. Different NuMA constructs, in which either N-or C-terminal domains were deleted, and the full-length construct were expressed in Escherichia coli, and the NuMA polypeptides were purified to homogeneity and allowed to assemble in vitro. Electron microscopy showed that NuMA can build multiarm oligomers by interaction of the C-terminal globular domains. Each arm of the oligomer corresponds to a NuMA dimer. Oligomers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 23 publications
3
114
0
6
Order By: Relevance
“…NuMA is multimeric. It may have as many as six microtubule-binding sites per assembled unit, and these units tend to polymerize (Harborth et al, 1999). Previous models for its function in aster and pole assembly proposed that it uses these microtubule binding sites to cross-link microtubules at the poles, perhaps acting in concert with cytoplasmic dynein (Merdes et al, 1996;Fant et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NuMA is multimeric. It may have as many as six microtubule-binding sites per assembled unit, and these units tend to polymerize (Harborth et al, 1999). Previous models for its function in aster and pole assembly proposed that it uses these microtubule binding sites to cross-link microtubules at the poles, perhaps acting in concert with cytoplasmic dynein (Merdes et al, 1996;Fant et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotes do not contain PARPs, so recombinant proteins expressed in them are free of pADPr modifications. Full-length NuMA is highly insoluble as a pure protein (Harborth et al, 1999), so we split it into three fragments for expression and purification (Figure 6,top). These approximately correspond to the domain organization of NuMA, representing the C-and N-terminal globular domains, and to a central, coiled-coil rod domain.…”
Section: A Recombinant Numa Fragment Binds Directly To Padprmentioning
confidence: 99%
“…This avoids the C-terminus-mediated oligomerization (Harborth et al, 1999) with endogenous protein that can complicate interpretations of localization. In this NuMA-knockout background, full-length NuMA ('FL') localized to spindle minus-ends, as did a bonsai construct ('N-C') with most of the central coiled-coil removed ( Figure 6B).…”
Section: Numa Localizes To Minus-ends Independently Of Known Minus-enmentioning
confidence: 99%
“…Unlike known dynein activators, NuMA is thought to not only homodimerize but also oligomerize into higher order assemblies (Harborth et al, 1999;Saredi et al, 1997). NuMA's oligomerization ability suggests that it could assemble teams of motors and invites a comparison to motor-clustering in microdomains on large cellular cargoes, like phagosomes (Rai et al, 2016).…”
Section: Numa As Mitotic Dynein Adaptor or Activatormentioning
confidence: 99%
“…After nuclear envelope breakdown, during prometaphase, NuMA associates with cytoplasmic dynein and uses its minus-end-directed motor activity to accumulate at spindle poles (Merdes et al, 1996;Merdes et al, 2000), where it focuses microtubule minus ends and tethers centrosomes to the body of the spindle. NuMA has been shown to selfassemble into large matrices Saredi et al, 1997;Harborth et al, 1999;Gueth-Hallonet et al, 1998) and electron microscopy has demonstrated that, once NuMA localizes to spindle poles, it becomes part of an insoluble matrix closely associated with microtubule minus ends (Dionne et al, 1999). NuMA can cross-link microtubules in vitro (Haren and Merdes, 2002), suggesting that its essential…”
Section: Introductionmentioning
confidence: 99%